Titrimetric and spectrophotometric assay of diethylcarbamazine citrate in formulations using iodate and iodide mixture as reagents - Nagaraju Swamy; Kudige Nagaraj Prashanth; Kanakapura Basavaiah (Universidade de São Paulo, 2015)
One titrimetric and two spectrophotometric methods are proposed for the determination of diethylcarbamazine citrate (DEC) in bulk drug and in formulations using potassium iodate and potassium iodide as reagent. The methods employ the well-known analytical reaction between iodate and iodide in the presence of acid. In titrimetry (method A), the drug was treated with a measured excess of thiosulfate in the presence of unmeasured excess of iodate-iodide mixture and after a standing time of 10 min, the surplus thiosulfate was determined by back titration with iodine towards starch end point. Titrimetric assay is based on a 1:3 reaction stoichiometry between DEC and iodine and the method is applicable over 2.0-10.0 mg range. The liberated iodine is measured spectrophotometrically at 370 nm (method B) or the iodine-starch complex measured at 570 nm (method C). In both methods, the absorbance is found to be linearly dependent on the concentration of iodine, which in turn is related to DEC concentration. The calibration curves are linear over 2.5-50 and 2.5-30 µg mL-1 DEC for method B and method C, respectively. The calculated molar absorptivity and Sandell sensitivity values were 6.48×103 L mol-1 cm-1 and 0.0604 µg cm-2, respectively, for method B, and their respective values for method C are 9.96×103 L mol-1 cm-1 and 0.0393 µg cm-2. The intra-day and inter-day accuracy and precision studies were carried out according to the ICH guidelines. The methods were successfully applied to the analysis of DEC formulations.